Caracterización de indicadores de detección de glaucoma con los equipos OCT Spectralis y campímetro Humphrey II en pacientes altos miopes y altos miopes glaucomatosos del Hospital Clínico Universidad de Chile - Rojas B., Felipe; Aguilar V., Mauricio; Meza M., Karl; Pinto C., Catalina; Verdugo H., Paula (Revista Hospital Clínico Universidad de Chile, 2019)
Purpose: Characterize and describe glaucoma index parameters of the results of visual exams, Optical Coherence Tomography and Visual Field, in high myopic subjects with and without the pathology. Method: Cross sectional and observational study of 39 eyes, 15 high myopic with glaucoma y 24 high myopic without it. Visual Field (VF) were performed, where the global index between both groups were analyzed; Mean Deviation (MD), Model Standard Deviation (MSD) and Visual Field Index (VFI), beside Optical Coherence Tomography (OCT), in which the thickness of the ganglion cells layer (GCL) inside 3 central mm was compared. Results: The results were satisfactory, demonstrating different characteristics between the high myopic group with glaucoma and without it, both in VF and OCT exams. It was obtained in the VF analysis difference in average MD of -4,92 dB + 3,71 (p<0,05); difference in average DSM of 2,01 dB + 2,85 (p>0,05) and VFI with Friedman Test 10,29 (p>0,05). The statistical OCT analysis, when comparing GCL, observed that the Temporary sector (T) had a statistically significant decrease (p<0,05). Conclusions: To continue studies in this investigative line, can expand the knowledge in this area, mainly in the study of the GCL.